A switch from joint to individual taxation is welfare improving - André Decoster; Peter Haan (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this paper we empirically derive the welfare effects of a shift from joint taxation with full income splitting to a revenue neutral system of individual taxation in Germany. For the empirical welfare evaluation we estimate the preference heterogeneity in the population and use normative welfare concepts proposed in Fleurbaey (2006) to solve the difficulties of comparison between, and aggregation of heterogeneous individuals and households. We show that, irrespective of the individual welfare measure we use, individual taxation would on average increase individual welfare. Moreover, as far as the aggregation is concerned, we show that any social planner, ranging from a utilitarian to a Rawlsian one, would come to the same conclusion: a policy change which replaces joint taxation with full splitting by individual taxation, would be welfare improving.
Keywords: C35; D63; D78; H24; H31; J22; 330; Taxation of couples; welfare measures; labour supply; preference heterogeneity